2012
DOI: 10.1152/ajpgi.00433.2011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cardiac preload reduction and dobutamine on hepatosplanchnic blood flow regulation in porcine endotoxemia

Abstract: Takala J. Effects of cardiac preload reduction and dobutamine on hepatosplanchnic blood flow regulation in porcine endotoxemia. Am J Physiol Gastrointest Liver Physiol 303: G247-G255, 2012. First published May 3, 2012 doi:10.1152/ajpgi.00433.2011.-Insufficient cardiac preload and impaired contractility are frequent in early sepsis. We explored the effects of acute cardiac preload reduction and dobutamine on hepatic arterial (Qha) and portal venous (Qpv) blood flows during endotoxin infusion. We hypothesized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Therefore, if post-SCI hypoperfusion leads to ischemia, tissue damage and necrosis are likely to occur whereby the walls of the GI tract may become permeable, allowing bacteria to proliferate and translocate through the gut wall and into lymph nodes and blood vessels (6,32). With inadequate splanchnic perfusion, multiple organ failure and death may ensue (25). The development of episodic hypertension, a phenomenon associated with massive sympathetic discharge that is triggered by noxious visceral or sensory stimuli below the injury level (commonly referred to as autonomic dysreflexia; 24), may also provoke periods of GI hypoxia due to hyperreactivity of the mesenteric bed (47).…”
Section: Implications Of Gastrointestinal Vascular Dysregulationmentioning
confidence: 99%
“…Therefore, if post-SCI hypoperfusion leads to ischemia, tissue damage and necrosis are likely to occur whereby the walls of the GI tract may become permeable, allowing bacteria to proliferate and translocate through the gut wall and into lymph nodes and blood vessels (6,32). With inadequate splanchnic perfusion, multiple organ failure and death may ensue (25). The development of episodic hypertension, a phenomenon associated with massive sympathetic discharge that is triggered by noxious visceral or sensory stimuli below the injury level (commonly referred to as autonomic dysreflexia; 24), may also provoke periods of GI hypoxia due to hyperreactivity of the mesenteric bed (47).…”
Section: Implications Of Gastrointestinal Vascular Dysregulationmentioning
confidence: 99%
“…Furthermore, the buffer capacity seems to be related to degree of portal resistance [20,21] . Similar to liver cirrhosis, portal vein blood flow is also decreased during endotoxemia [22] , and the HABR is diminished or abolished time-dependently [22,23] . It has been reported that early administration of exogenous nitric oxide (sodium nitroprusside) during endotoxemia can dilate the hepatic artery and reverse the HABR, implying that the endotoxin-induced HABR dysfunction may result from a selective inhibition of vascular endothelial function [24,25] .…”
Section: Introductionmentioning
confidence: 98%
“…All this may interfere with hepatic arterial vasodilatation. Besides, the diminished or abolished HABR has also been manifested when systemic and splanchnic blood flows are critically reduced [23,30] . In early sepsis, such hypodynamic conditions may exist, and are often followed by a hyper-dynamic phase.…”
Section: Introductionmentioning
confidence: 99%